Role of Prescription Practice in Ensuring Patient Safety in the Primary Health-Care Settings in India - Satyaban Sahu; Arish Syed; Preet Verma; Rajesh R Singh; Shyama Nagarajan; Shiven Singh (Wolters Kluwer Medknow Publications, 2023)
"Completeness (a measure of adequacy)" and the "appropriateness (a measure of the quality of care)" are two dimensions of good prescription practice. The study assessed the prescription practices at the primary health centers (PHCs); to demonstrate the effect of individual and system-level factors, on adequacy and appropriateness of prescription practices, with special reference to e-prescription over manual prescription given the rising acceptance of teleconsultation in health care. A total of 600 manual and 1000 e-prescriptions were randomized using a probability-proportional-to-size sampling method to distribute/allocate samples across manual and e-prescriptions. Findings revealed that while adequacy and appropriateness of prescriptions depend on individual training and clinical practice; adequacy of prescription, especially the manual was compromised by systemic factors, such as nonavailability of space in a prescription, forcing doctors to prioritize documentation of diagnosis, advising tests, and prescribing medicines, over other details (chief complaints and examination findings).